2023
DOI: 10.1002/clen.202200370
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the possibility of PCCP mortar coating leaching and the impact on drinking water quality

Abstract: The objective of this article was to investigate the potential for the dissolution and leaching of certain chemical elements from the protective mortar coatings of prestressed concrete cylinder pipe (PCCP) into drinking water in the event of leakage and how this might affect the overall quality of the water delivered to consumers. The mortars as linings are also typically used for renovation of old pipes. Samples from three frequently used mortar coating mixtures underwent immersion in water after 28 days of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(69 reference statements)
0
0
0
Order By: Relevance
“…For everything mentioned in the previous paragraphs, the objective of the present investigation was to analized the anticorrosive efficiency of the reinforced steel AISI 316 SS in comparison to the steel AISI 1018 at being embedded in Sustainable Ecological Concrete (SEC) manufactured with partial substitutions of Portland Cement by combinations of SCBA and SF in 10%, 20%, and 30% exposed to the solution at 3.5% of MgSO 4 , as aggressive environment. This research contributes to the development of durability concretes and the use of agro-industrial and industrial wastes, and in the decrease of use of cement, what is going to impact the reduction of emissions of CO 2 from the cement industry, which is responsible for the 6% to 8% of the emissions of CO 2 at global level [42]- [46]. With the obtained results of corrosion potential (E corr ) and corrosion rate (I corr ), of the steels of the present research, it can be identified the mixture of concrete SEC that brings a higher protection or durability against corrosion for the presence in magnesium sulphate.…”
Section: Anticorrosive Efficiency Of the Aisi 316 Ss In Sustainable E...mentioning
confidence: 99%
“…For everything mentioned in the previous paragraphs, the objective of the present investigation was to analized the anticorrosive efficiency of the reinforced steel AISI 316 SS in comparison to the steel AISI 1018 at being embedded in Sustainable Ecological Concrete (SEC) manufactured with partial substitutions of Portland Cement by combinations of SCBA and SF in 10%, 20%, and 30% exposed to the solution at 3.5% of MgSO 4 , as aggressive environment. This research contributes to the development of durability concretes and the use of agro-industrial and industrial wastes, and in the decrease of use of cement, what is going to impact the reduction of emissions of CO 2 from the cement industry, which is responsible for the 6% to 8% of the emissions of CO 2 at global level [42]- [46]. With the obtained results of corrosion potential (E corr ) and corrosion rate (I corr ), of the steels of the present research, it can be identified the mixture of concrete SEC that brings a higher protection or durability against corrosion for the presence in magnesium sulphate.…”
Section: Anticorrosive Efficiency Of the Aisi 316 Ss In Sustainable E...mentioning
confidence: 99%